Financial and corporate governance determinants of dividend policy in family firms: A bibliometric analysis and future research agenda - Azekkar, Younes; Taghouti, Younes; Abidar, Brahim; Boustta, Omar; Ouafa, Khalid El (Edelweiss Applied Science and Technology, 2025)
This study conducts a systematic literature review of 63 peer-reviewed articles published between January 2008 and December 2023, sourced from the Scopus database, to examine the key determinants shaping dividend policies in family firms. The analysis reveals that financial factors, particularly profitability, leverage, and growth opportunities, serve as primary drivers of dividend decisions. In addition to these, non-financial determinants related to corporate governance, such as board independence, CEO duality, gender diversity, and board size, significantly influence dividend policy by mitigating agency conflicts and aligning the interests of controlling and minority shareholders. By integrating both financial and non-financial perspectives, the study offers a comprehensive understanding of the multifaceted mechanisms that govern dividend strategies in family-owned enterprises. Furthermore, a bibliometric analysis was performed using VOSviewer and RStudio to visualize the intellectual structure of the field, identify emerging research trends, and map scholarly collaborations. The findings provide critical insights for academics, practitioners, and policymakers seeking to strengthen governance frameworks and enhance financial decision-making within family business contexts.